An In - Vitro Agar Diffusion Study Comparing The Antimicrobial Activity Of Nanoseal With Some Other Endodontic Sealers - Kamal, Ali Burak (2010)
Complete elimination of microbes in teeth with an infected dental pulp is one of the main objectives of endodontic treatment. Endodontic sealers should have a wide antimicrobial spectrum and action time because of the polymicrobial characteristics of endodontic infections and to eliminate residual microorganisms unaffected by the effects of chemomechanical preparation and intracanal medication of endodontic treatment. The objectives of this study were 1) To evaluate the antimicrobial activity of NanoSeal ™, AH26 ™, Tubli-Seal ™, Sealapex ™ and Roeko-Seal ® against Enterococcus faecalis, Pseudomonas aeruginosa, Streptococcus mutans, Streptococcus sobrinus, and Escherichia coli in three incubation periods of 24 hours, 48 hours and 168 hours . 2) To compare the antimicrobial activity of the five sealers towards each type of microorganism in the three periods. 3) To compare the antimicrobial activity between the tested sealers towards each type of microorganism in the three periods.